2022
DOI: 10.1051/0004-6361/202243328
|View full text |Cite
|
Sign up to set email alerts
|

Nearby galaxies in the LOFAR Two-metre Sky Survey

Abstract: Context. Magnetic fields, which regulate stellar feedback and star formation in galaxies, are key to understanding galaxy evolution. Aims. We probe the origin of magnetic fields in late-type galaxies, measuring magnetic field strengths and exploring whether magnetic fields are only passive constituents of the interstellar medium or whether, being part of the local energy equilibrium, they are active constituents. Methods. We measure equipartition magnetic field strengths in 39 galaxies from LoTSS-DR2 using LOF… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 87 publications
1
6
0
Order By: Relevance
“…With these values, we obtain the values in Table 7. These rough estimates are consistent, at the order-of-magnitude level, with those of Heesen et al (2023), who estimate a range 4.7-7.4 μG for  B . Moreover, we generally find…”
Section: Scaling Relation Proportionality Coefficientssupporting
confidence: 85%
See 2 more Smart Citations
“…With these values, we obtain the values in Table 7. These rough estimates are consistent, at the order-of-magnitude level, with those of Heesen et al (2023), who estimate a range 4.7-7.4 μG for  B . Moreover, we generally find…”
Section: Scaling Relation Proportionality Coefficientssupporting
confidence: 85%
“…This can be taken as further evidence that turbulence driving in nearby galaxies is dominated by SN Notes. Fitting data for the total magnetic field strength in multiple galaxies (estimated assuming energy equipartition with cosmic rays), Heesen et al (2023) obtain  B in the range 4.7-7.4 μG. Our model coefficients are generally of the same order of magnitude as theirs.…”
Section: Scaling Relationsmentioning
confidence: 66%
See 1 more Smart Citation
“…Two notable outliers with a large transport length are NGC 4254 and NGC 4548 with l CRe > 5 kpc. Those values are larger than the values ≤3.8 found for field galaxies at 144 MHz in Heesen et al (2023b). This is likely due to the significant contribution of RPS (and in the case of NGC 4254, also the tidal perturbation, Vollmer et al 2005a) to the CRe-transport, a scenario also suggested by Ignesti et al (2022b).…”
Section: Spatially Resolved Radio-sfr Analysismentioning
confidence: 64%
“…We now calculate the electron lifetime taking into account synchrotron and inverse Compton losses. For that we use the average total (mostly random) equipartition magnetic field strength of B = 12.0 ± 2.6 µG (Heesen et al 2023). The radiation energy density U rad is the sum of two parts: the CMB energy density, which can be measured directly, and the total energy density U TIR with an additional contribution of stellar light.…”
Section: Cosmic-ray Electron Transport Lengthsmentioning
confidence: 99%